(untitled) (Research, Society and Development, 2020)
The Ethnoictiology, an ethno-sciences, has been used as a tool in the management of fish stocks because it provides information about the biological and behavioral aspects of marine organisms. Artisanal fishermen have got a ecological knowledge about most of the species they explore, being able to express their opinions and suggest alternatives so that exploitation of resources takes place in a sustainable way so the objective of this work is to verify fishermen’s knowledge of six fishing communities of Angra dos Reis about variations in abundance of the groups of fish they exploit. The 28 fishermen that took part in the study answered a socioeconomic and an ethnoictiological questionnaire. From the results we can see that the artisanal fishing on site is declining due to the high average age of fishermen and the lack of investment in infrastructure on Ilha Grande bay. The fishermen mainly observed a decrease of whitemouth croaker and Brazilian sardine, which have been overexploited by industrial fishing, resulting in the diminution of Atlantic chub mackerel, blue runner/horse-eye jack and Atlantic moonfish/lookdown, which are part of its companion fauna. Therefore, alternatives of fishery management are necessary, which prioritize not only ecological aspects, but also sociocultural aspects of artisanal fishermen.